Strengthening the Economy through Family Skills Enhancement Training - Rahayu, Sri; Yudi, Yudi; Rainiyati, Rainiyati; Hamzah, Hamzah; Tiswiyanti, Wiwik; Khaldun, Muhammad Hafidz Ibnu (Jurnal Karya Abdi Masyarakat, 2025)
Each family member must have the skills to support each other in improving the family’s welfare. Husbands and fathers, as heads of the family, must be able to manage all family activities. As the family’s financial manager, the mother has the authority to manage all family income well so that it can be used to meet the family’s needs. Mothers and children can also contribute to finding sources of revenue for the family. This community service activity (PkM) is carried out by improving the skills of mothers and young women to manage family finances and strengthen business skills as an alternative source of family income. The business skills provided are sewing traditional community clothing at the activity partner’s location. All participants were very enthusiastic about participating in the training activities. This was evident from the discussion and the many questions asked by group members. Members and prospective group members hope that training activities to improve skills for women can continue to be carried out in the future.